The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1159/000147739
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Denervation on Morphogenesis of the Rat Fungiform Papilla

Abstract: In an attempt to elucidate the effects of denervation on development and maintenance of the structure of the fungiform papilla, unilateral neurectomy of the chorda tympani-lingual nerve of rats was performed at day 1 and at weeks 1, 2, 3, 4, 7, and 10 after birth. Specimens were obtained at days 3, 7 and 10, weeks 2, 3, 4, 6, and 8, and months 3 and 4 after neurectomy for examination by light and scanning electron microscopy. At first, the fungiform papillae were atrophic, then progressed to forms resembling f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
48
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 1 publication
3
48
0
Order By: Relevance
“…This reduction was similar to that reported previously (Fan et al, 2004). Loss of gustatory innervation during development can reduce the numbers of taste buds and fungiform papillae (Hosley et al, 1987;Nagato et al, 1995;Sollars and Bernstein, 2000;Sollars et al, 2002;Sollars, 2005). Thus, one explanation for the present findings is that neurotrophins function to maintain gustatory neurons via the p75 receptor.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This reduction was similar to that reported previously (Fan et al, 2004). Loss of gustatory innervation during development can reduce the numbers of taste buds and fungiform papillae (Hosley et al, 1987;Nagato et al, 1995;Sollars and Bernstein, 2000;Sollars et al, 2002;Sollars, 2005). Thus, one explanation for the present findings is that neurotrophins function to maintain gustatory neurons via the p75 receptor.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with a developmental role for p75. Removal of gustatory innervation during development results in the loss of both fungiform papillae and taste buds, while removal of innervation during adulthood causes taste bud loss but does not affect the fungiform papilla (Oakley et al, 1990;Nagato et al, 1995;Sollars, 2005). Quantification of fungiform taste buds over the course of development will be necessary to provide unequivocal evidence for a developmental role for p75 for fungiform papillae and taste buds.…”
Section: Discussionmentioning
confidence: 99%
“…Neonatal chorda tympanilingual nerve transection in rats leads to a deficit in fungiform papillae development (i.e., fungiform papillae are nondistinguishable from filiform papillae) and loss of taste buds (Nagato et al, 1995). It has also been shown that gustatory fibers are more efficacious in maintaining taste buds and gustatory papillae than other type of nerves (Hård af Segerstad et al, 1989;Oakley et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Filiform-like papillae are easily distinguished from actual filiform papillae because the cornified epithelial protrusion is larger than that of filiform papillae and the ''cone'' is typically angled in a direction atypical of the orientation of the filiform papillae [ Fig. 1(C); Ganchrow and Ganchrow, 1989;Hård af Segerstad et al, 1989;Oakley et al, 1990Oakley et al, , 1993Nagato et al, 1995;Iwasaki et al, 1997;Sollars, et al, 2002].…”
Section: (B)]mentioning
confidence: 99%
“…The indentation, hillock, and pore are generally no longer visible, and the epithelial surface appears flattened (Parks and Whitehead, 1998). In some instances, papillae become heavily keratinized and form a spike-shaped protrusion that resembles large filiform papillae and thus are termed ''filiform-like'' (Hård af Segerstad et al, 1989;Oakley et al, 1990;Nagato et al, 1995;Sollars et al, 2002). However, when transection is performed in the adult rat, the majority of taste buds regenerate upon reinnervation by the CT, approximately 40 days following transection (St. John et al, 1995;Kopka et al, 2000).…”
mentioning
confidence: 99%